TINJAUAN HUKUM ISLAM TERHADAP PRAKTIK ISBAT NIKAH SEBAGAI UPAYA LEGALISASI PERNIKAHAN SIRI DI PENGADILAN AGAMA MAKASSAR KELAS IA - Hijra Wati; Zulfahmi Alwi; Musyfikah Ilyas (Universitas Islam Negeri Alauddin Makassar)
In practice, it is often found that a marriage without registration is made, in order to make the marriage legal in the state and have legal power, it is possible to apply for an Isbat of Marriage so that the marriage of siri can be determined by the Isbat of Marriage to the Religious Courts, so that marriages that are held in a serial manner can be legalized. So that when the Religious Courts have received the application for Isbat Marriage, the Office of Religious Affairs can record the marriage and obtain a marriage certificate as proof of the legality of the marriage. Applications for Isbat Marriage submitted can sometimes be rejected with certain considerations by the Panel of Judges in the Religious Courts. So that it will make marriages carried out in a serial manner still have no legal force. The author has examined the Legal Basis and Judges' Considerations in Granting the Application for Marriage Isbat as an Effort to Legalize Siri Marriage at the Makassar Religious Court Class IA and the View of Islamic Law on the Legalization of Siri Marriage through the Practice of Isbat Nikah at the Makassar Religious Court Class IA. The type of research in this thesis is descriptive qualitative in the form of field research or Field Research which focuses on collecting and data information found in the field, using a normative and juridical syar'i approach which aims to obtain law empirically by going into the field. The data collection methods used are observation, interviews, and documentation. With data processing and analysis techniques, it is carried out through three stages, namely data reduction, data presentation, and drawing conclusions. The results showed that the main considerations made by the judge in the results of the study were that the judge's considerations in granting the application for the practice of siri marriage isbat, namely the marriage has fulfilled the requirements and the pillars of marriage, that it is true that the applicant is married and there is no previous marriage bond, that the applicant is not blood related. which can prevent his marriage and to take care of other documents related to the interests of the applicant. And according to Islamic law, isbat marriage is allowed in Islamic law because it is a marriage ratification that has been carried out in accordance with his religion and belief but is not recorded at the office of religious affairs and the authorized marriage registration officer. Keywords: Judge's Consideration, Marriage Isbat, Religious Court, Islamic Law